Effect of Variations of Roasting Temperature on the Physicochemical Properties of Robusta Coffee (Coffea canephora L.) - Muhammad Rizky Ramanda; Azzahra Fali Prameswari; Masayu Nur Ulfa (The University of Lampung, 2024)
Robusta coffee has become the most planted coffee in Indonesia and a vital commodity. Robusta coffee is characterized by a more caffeine content, bitter taste, and slightly more acidic compared to that of Arabica coffee. The roasting process is important factors contributing to shape taste, aroma, and the physical characteristics of coffee beans. This study seeks to compare the physicochemical properties of Robusta coffee originated from West Lampung and Tanggamus, and to assess the impact of roasting temperature (light at 190°C, medium at 200°C, and dark at 210°C). Measurement was conducted in duplicate. The findings indicated significant differences (p<0.05) in ash content, moisture content, and pH between coffee from West Lampung and Tanggamus, while color and caffeine content did not differ significantly (p>0.05). The geographic origin of coffee beans influences their physicochemical properties. Moreover, all examined parameters (ash content, moisture content, pH, color, and caffeine content) show a direct relationship with the roasting temperature. Consequently, roasting temperature plays a pivotal role in shaping the physicochemical properties of coffee beans. Keywords: Caffeine, Coffee, Region, Roasting, Temperature.